Patogenitas Nematoda Entomopatogen Heterorhabditis spp. Terhadap Larva Spodoptera litura - Hawwa' Cahya Maulida; Saiku Rokhim; Erna Zahro’in (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
Spodoptera litura is a pest in vegetable plants that attacks the leaves and stems. Damage arising from the attack of S. litura can decrease the productivity of plants. Synthetic pesticides are often used in controlling the population of S. litura, but synthetic pesticides have a high negative impact. Potential entomopathogenic nematode Heterorhabditis spp. believed to be effective for controlling pest populations. This study aims to find out the pathogenic value of entomopathogenic nematode Heterorhabditis spp. to the larvae of S. litura. Based on the results obtained Heterorhabditis spp. has a positive influence in causing mortality in the larvae of S. litura. Heterorhabditis spp. mortality of up to 42%. Symptoms indicated by larvae of S. litura affected by Heterorhabditis spp. among them the behavior becomes passive, the body becomes flaccid, the cuticle turns red and the tissues inside the body are destroyed. Obtained pathogenicity value Lc 50 Heterorhabditis spp. 7,690 IJ/ml, as for the factors affecting Heterorhabditis spp. such as humidity, temperature, pH, and light intensity.Keywords – Entomopathogenic Nematodes, Pathogenicity, Spodoptera litura